2011
DOI: 10.21608/jpp.2011.85582
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Some Maize Hybrids Cultivated With Different Plant Densities

Abstract: Two field experiments were carried out at the Agric. Exp. Sta. Fac. Agric., Cairo Univ., Giza, during 2009 and 2010 seasons to study the response of three hybrids of maize, Zea mays L. (S.C. 10, S.C. 122 and T.W.C. 321) to four plant densities (4.76 plants/m 2 , 5.56 plants/m 2 , 6.67plants/m 2 and 8.33 plants/m 2) on yield and yield components. Results showed that, significant differences between maize hybrids in plant height, number of ears/plant, barren %, LAI, number of kernels /row, grain weight/ear and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
3
2
0
Order By: Relevance
“…The increases in grain yield when plants were sown at lowest hill spacing (15 cm) may be due to increase in number of rows/ear and number of grains/ear. These results in good agreement with those reported [4,26]. This may be due to more approach uniformity by sown at 15 cm hill spacing.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The increases in grain yield when plants were sown at lowest hill spacing (15 cm) may be due to increase in number of rows/ear and number of grains/ear. These results in good agreement with those reported [4,26]. This may be due to more approach uniformity by sown at 15 cm hill spacing.…”
Section: Discussionsupporting
confidence: 92%
“…In this respect, [1,2] summarized that for obtaining a higher maize yield and net income, maize hybrids had different responses to agronomic characters and grain yield. [3,4] showed a significant difference between maize hybrids in plant height, No. of ear/plant, barren %, LAI, No.…”
Section: Introductionmentioning
confidence: 95%
“…Edmeades et al (2000) found that high plant densities enhance interplant competition for assimilates, particularly during the period bracketing silking, favoring epical dominance and decreasing the ratio of ear to tassel growth rate. Similar results were reported by Zeidan et al (2006), Maddonni et al (2006), Shakarami & Rafiee (2009), Gozubenli (2010), EL-Metwally et al (2011) and Sarwar et al (2016).…”
Section: Yield Attributessupporting
confidence: 90%
“…Meanwhile, a progressive increase in plant height was obtained with progress of maize-plant development towards physiological maturity with variable rate depending on stage of growth Pandey et al, (2000), Tajul et al, (2013), Shaalan et al, (2015), Kelly et al, (2015) and Akinnuoye-Adelabu and Modi (2017). In the mean times, our results presented here for plant density effects on plant height were in harmony with the results of EL-Metwally et al, (2011), El-Shahed et al, (2013 and El-Sobky and El-Nagar (2016), since, their results showed that with increasing plant density, plant height was not affected. Similar results for this trait were reported by Turgut et al, (2005), Carpici et al, (2010), Baghdadi et al, (2012), Karashin (2014), Kumar et al, (2016).…”
Section: Plant Characterssupporting
confidence: 92%
“…On the other hand, LAI varied among Egyptian maize hybrids. EL-Metwally et al, (2011), El-Shahed et al, (2013 and Hegab et al, (2019), illustrated that, SC10 gave the highest LAI (3.48 m 2 m -2 ), whereas, TC 352 gave the least LAI (2.71 m 2 m -2 ) Khan et al, (2012) and Baghdadi et al, (2012) noticed that, LAI progressively increased up to 65 DAS and then start declining. As plant density increased, leaf area index LAI increased according Kumar and Walia (2003), Bruns and Abbas (2006), Abuzar et al, (2011), Khalil et al, (2010), Baghdadi et al, (2012), El-Shahed et al, (2013), El-Hosary et al, (2019 and Salifu and Dóka (2019).…”
Section: Growth Parametersmentioning
confidence: 98%